Pengelolaan Air Limbah Hotel Dan Pemanfaatannya Dalam Pembangunan Pariwisata Berkelanjutan - Septi Ayu Andini; I Nyoman Sukma Arida (JURNAL DESTINASI PARIWISATA, 2019)
Nusa Dua tourism area shaded by PT. Indonesia Tourism Development Corporation (ITDC) has been known as a center of international tourism area that reflects the characteristics of international standards for all facilities built. ITDC has an integrated wastewater treatment system called "Lagoon", which accommodates all waste from tourism and hotel activities in Nusa Dua Tourism Area to be reused. It is interesting to investigate because in the future this research can be a study material in waste water management produced by tourism accommodation, so that environmental pollution generated by wastewater disposal from tourism activities can be minimized. The research method used in this research is qualitative data analysis technique to know how waste water management of hotel in ITDC. Data source, from primary data and secondary data. Data collection techniques using observation methods, interviews, documentation and research instruments in the form of interview guidelines. Determination of informants in this study using purposive sampling. The results obtained are the existing condition of hotel wastewater treatment in Lagoon and its utilization is seen from the wastewater treatment system, irrigation water production system, the amount of clean water and waste generated, the efficiency of wastewater treatment and the utilization produced by wastewater treatment. Keywords: Accommodation, Waste Treatment, Sustainable Tourism Development